Complete life cycle of a pennellid Peniculus minuticaudae Shiino, 1956 (Copepoda: Siphonostomatoida) infecting cultured threadsail filefish, Stephanolepis cirrhifer - Ismail, Norshida; Ohtsuka, Susumu; Maran, Balu Alagar Venmathi; Tasumi , Satoshi; Kassim, Zaleha; Yamashita, Hirofumi (EDP Sciences, 2013)
The complete life cycle of a pennellid copepod Peniculus minuticaudae Shiino, 1956 is proposed based on the discovery of all post-embryonic stages together with the post-metamorphic adult females infecting the fins of threadsail filefish Stephanolepis cirrhifer (Monacanthidae) cultured in a fish farm at Ehime Prefecture, Japan. The hatching stage was the infective copepodid. The life cycle of P. minuticaudae consists of six stages separated by moults: the copepodid, four chalimi and adult. In this study, the adult males were observed frequently in precopulatory amplexus with various stages of females however, copulation occurs only between adults. Fertilized pre-metamorphic adult females carrying spermatophores may detach from the host and settle again before undergoing massive differential growth into the post-metamorphic adult female. Comparison of the life cycle of P. minuticaudae has been made with three known pennellids: Lernaeocera branchialis (Linnaeus, 1767), Cardiodectes medusaeus (Wilson, 1908) and Lernaeenicus sprattae (Sowerby, 1806). Among the compared species, P. minuticaudae is the first ectoparasitic pennellid to be discovered to complete its life cycle on a single host without any change in infection site preferences between infective copepodid and fertilized pre-metamorphic female.